2010
DOI: 10.4103/0974-8490.60580
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant and anxiolytic evaluation of leaf extracts ofOcimum gratissimum, a culinary herb

Abstract: Anticonvulsant and anxiolytic activities of leaf extracts and fraction of Ocimum gratissimum L. (Lamiaceae) were studied using seizures induced by pentylenetetrazol and open-field tests in mice. The results showed that the extracts and fraction increased the latency of tonic and tonic-clonic seizures and death and elicited 50% protection against mortality. In the open-field test, the extracts and fraction decreased the frequency of line crossing, center square entries, rearing against a wall and grooming, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 22 publications
0
21
0
4
Order By: Relevance
“…This plant has been prepared in a variety of forms for consumption as food spice or traditional herb in many Asian and African countries since ancient time 12-19. Recent studies also demonstrate many therapeutic activities of the OG aqueous extract (OGE), including anti-inflammation 17, 20, analgesic and spasmolytic activities 21, antidiarrheal activity 13, antihyperglycemic activity 22, and improvement of phagocytic function 23.…”
Section: Introductionmentioning
confidence: 99%
“…This plant has been prepared in a variety of forms for consumption as food spice or traditional herb in many Asian and African countries since ancient time 12-19. Recent studies also demonstrate many therapeutic activities of the OG aqueous extract (OGE), including anti-inflammation 17, 20, analgesic and spasmolytic activities 21, antidiarrheal activity 13, antihyperglycemic activity 22, and improvement of phagocytic function 23.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters assessed were climbing behavior and frequency of rearing (Moore and Axton, 1998). The apormorphine induced streotypy was measured and scored as follows: 0=Absence of Stereotypy; 1=Occasional Sniffing; 2=Occasional Gnawing; 3=Frequent Gnawing; 4=Continuous Gnawing; 5=Gnawing Intensively and Staying on the Same Spot (Okoli et al, 2010a). A significant decrease in climbing scores was observed in Ficus platyphylla (Chindo et al, 2015) and Securinega virosa .…”
Section: (C) Other Behavioral Studies (I) Apormorphine Induced Strementioning
confidence: 99%
“…Similarly, recent studies report leaf extracts from ethanolic and aqueous tulsi protects rats from stress-induced cardiovascular changes [48, 49]. Studies in animal models have further shown that the leaf extract of tulsi possesses anticonvulsant and anxiolytic activities [50, 51]. Several animal studies conducted over the past fifty years report that ingestion of tulsi leaves improves both glucose and lipid profiles in normal and diabetic-induced animal models [36, 38, 52–58].…”
Section: Introductionmentioning
confidence: 99%